Family Mediation in Turkish Legal History from Mecelle to Present: An Analysis in the Context of Conciliatory Justice Theory - Muhammed Mansur Karadağ (Darulfunun Ilahiyat)
In the constitutional frameworks of modern states, the protection of the family holds a significant place among the state’s positive obligations. Resolving family disputes through conciliatory methods is considered within the scope of this obligation, as it both promotes social harmony and strengthens the institution of the family. Indeed, many countries today have enacted regulations that enable the resolution of family disputes through alternative dispute resolution (ADR) methods, thereby developing effective mechanisms in this field. In Turkish legal history, from the Mecelle-i Ahkâm-ı Adliyye to the present, alternative dispute resolution methods such as mediation and arbitration have been employed to establish social harmony and conciliatory justice. This study examines the historical evolution of these methods, assesses their applicability in family law, and offers solutions to contemporary legal challenges based on past experiences. Uncovering the historical roots of family mediation and arbitration systems is crucial for identifying shortcomings in past practises and developing an effective resolution model by addressing these deficiencies. Accordingly, alternative dispute resolution methods in Turkish legal history are categorized and analyzed under three main headings: judicial mediation, mediation-arbitration, and direct mediation. Finally, the contributions and shortcomings of these methods to the legal system from the Mecelle era to the present are evaluated, and a model draft law for resolving family disputes is proposed.